THE ARMED FORCES AND THE CURRENT MODEL OF SOCIAL RESPONSIBILITY - Ruiz-Rico Ruiz, Catalina (Journal of the Spanish Institute for Strategic Studies, 2018)
The Armed Forces are currently developing a model of social responsibility inthe fields of human rights, the environment, equality and efficiency, amongothers. The leadership shown by the Armed Forces in the area of socialresponsibility stems from the adoption of sustainable measures and measuresfor modernization in connection with other institutions and administrationswhile respecting their own singularities. Social responsibility outreach takesplace in foreign operations and in national operations with actions that gobeyond mere compliance with legislation in force.